TRANSLANGUAGING IN BALANCED LITERACY: A CASE STUDY OF EARLY ELEMENTARY CLASSROOMS - Heni Suryani; Dyah Lyesmaya; Barkah Barkah (Program Studi PGSD Universitas Flores, 2025)
This qualitative case study investigates how translanguaging can be purposefully integrated within a balanced literacy framework in early primary classrooms in multilingual Indonesia. Conducted at a private elementary school in Sukabumi (Grades 1–3) where most students speak Sundanese at home and Indonesian at school, the study triangulates classroom observations (mini-lessons in phonics/phonology, dialogic read-alouds, shared/guided reading, independent reading), semi-structured interviews, and instructional artifacts (lesson plans, phonics progressions, running records, anecdotal notes). Findings show that when translanguaging is designed with clear micro-instructional goals—especially for cross-language phoneme contrasts, pre-teaching academic vocabulary, and brief think-alouds—teachers maintain and even strengthen the “balance” between explicit foundational skills (phonemic awareness, phonics, decoding, fluency, vocabulary) and meaning-making practices. Specifically, short, targeted use of the home language followed by immediate re-anchoring to Indonesian, supported by multimodal scaffolds (articulatory gestures, bilingual anchor charts, word cards), was associated with improved grapheme–phoneme accuracy, higher self-correction rates, and increased proportions of inference-based responses referenced to the text. Effects varied by learner profiles and text genre: emergent readers dominant in Sundanese benefited most in phonics and decoding, while bilingual or Indonesian-dominant students showed gains in vocabulary precision and inferencing, particularly with informational texts. The study proposes practical design rules—limit dose (1–2 sentences), re-anchoring to target language, and assessment-informed decisions—to minimize over-translation and align translanguaging with phonics and comprehension goals. The contribution is both conceptual (an operational model for integrating translanguaging into balanced literacy) and practical (observable indicators and routines aligned with the Indonesian curriculum). Limitations include a single-site scope and short duration; future work should examine longitudinal effects, varied home languages, and optimized “dosage” through small-scale design experiments.